Assessing the association between the Mediterranean, Dietary Approaches to Stop Hypertension and Mediterranean-DASH Intervention for Neurodegenerative Delay dietary patterns, structural connectivity and cognitive function - Arnoldy, Lizanne; Gauci, Sarah; Young, Lauren M.; Macpherson, Helen; Civier, Oren; Scholey, Andrew; Pipingas, Andrew; White, David J. (British journal of nutrition, 2025)
The rising incidence of neurodegenerative diseases in an ageing global population has shifted research focus towards modifiable risk factors, such as diet. Despite potential links between dietary patterns and brain health, inconsistencies in neuroimaging outcomes underscore a gap in understanding how diet impacts brain ageing. This study explores the relationship between three dietary patterns – Mediterranean, Dietary Approaches to Stop Hypertension (DASH) and Mediterranean-DASH Intervention for Neurodegenerative Delay – and cognitive outcomes as well as brain connectivity. The study aimed to assess the association of these diets with brain structure and cognitive function, involving a middle-aged healthy group and an older cohort with subjective cognitive decline. The study included cognitive assessments and diffusion-weighted MRI data to analyse white matter microstructural integrity. Participants comprised fifty-five older individuals with subjective cognitive decline (54·5 % female, mean age = 64) and fifty-two healthy middle-aged individuals (48·1 % female, mean age = 53). Age inversely correlated with certain cognitive functions and global brain metrics, across both cohorts. Adherence to the Mediterranean, DASH and Mediterranean-DASH Intervention for Neurodegenerative Delay diets showed no significant cognitive or global brain metric improvements after adjusting for covariates (age, education, BMI). Network-based statistics analysis revealed differences in brain subnetworks based on DASH diet adherence levels in the subjective cognitive decline cohort. In the healthy cohort, lower white matter connectivity was associated with reduced adherence to Mediterranean-DASH Intervention for Neurodegenerative Delay and DASH diets. Ultimately, the study found no strong evidence connecting dietary patterns to cognitive or brain connectivity outcomes. Future research should focus on longitudinal studies and refine dietary assessments.